Preschool/Pre-Kindergarten Education Promoting Student Performance in Later Years: A Qualitative Perspective - Carla J. Thompson; Giang-Nguyen Thi Nguyen (International Journal of Emerging Issues in Early Childhood Education, 2021)
A thoughtful decision confronting parents considering pre-kindergarten or pre-school programs across the United States provided from the literature has focused on school readiness of children within the pre-kindergarten years. Prior to children moving into kindergarten, parents are often concerned with the related potential for increased student achievement and student performance of these children in later years. Public opinion concerning the “worth” of preschool education as a readiness provider for preparing children to enter kindergarten adequately prepared for learning has been a topic of dissention among educators and parents for more than a decade. This qualitative study involved conducting structured interviews with five educators (two pre-school teachers, two kindergarten teachers, and one early learning district administrator) from the same school district located in the southeast region of the United States. The current qualitative study focused on eight specific interview questions generated from the literature review. Each of the eight interview question responses was examined relative to specific criteria, positioning, and information aligned from the related literature. Resulting literature analyses and discussions provide specific viewpoints from the interviews of the five educators regarding the merits and potential worth of early education experiences. Implications of the study findings involve describing potential future research efforts aimed at examining influences of early education or preschool experiences related to students’ performance levels and attitudes relative to later school achievement.